Challenges faced by the Emirati family during the distance education period in light of the Covid 19 pandemic: A qualitative study on a number of mothers in the Emirate of Sharjah - AlBanna, Ruqayia; AlAlawi, Aisha; Abual-Khair, Omaima (Al-Adab Journal, 2023)
The current study aimed to identify the most important challenges faced by the Emirati family during the distance of education period in light of the Covid 19 pandemic since the beginning of the crisis until now, and the consequent efforts made by these families in order to keep pace with the emerging situation with distance education. The study relied on the qualitative descriptive approach, and used the in-depth interview guide as a main tool for the study. It was applied to an intentional (non-probabilistic) sample of mothers who have children studying at various levels of basic, secondary and university education from the Emirate of Sharjah in the United Arab Emirates, and the sample size was (30) individuals.. The results of the study revealed that all families (the sample of the study) made an extra effort to keep pace with distance education, and the study also indicated that mothers who have children in the pre-school and basic education stage have made more effort to follow up their children during the distance study period than others. Especially the working mothers, while the results indicated that the greatest effort that the working mothers endured falls on the category of working mothers who have children in the basic and preparatory education stages, i.e. grades (1-9), more than them in the advanced stages such as the tenth and eleventh grades. The twelfth and twelfth and university education by virtue of the knowledge of children in these stages of how to use e-learning techniques more than the children in the early stages of study. The study came out with a number of recommendations, the most important of which are: the importance of holding training workshops for mothers on how to use educational platforms, and the necessity of having electronic educational guides for the guardian to help him follow up his children, especially children in the pre-school stages, and basic education grades (1-9).